Pelatihan Public Speaking Upaya Meningkatkan Percaya Diri Remaja - Nurul Makrifah; Moh. Toyyib (STIT Al - Ibrohimy Bangkalan, 2024)
Inability to communicate can cause someone to be insecure when appearing in public. For students of SMK Darur Rohman who have a fear of speaking in public, a feeling of panic will arise that is very disturbing to the mind. Before starting to speak in public, the bodies of students of SMK Darur Rohman who are not ready will begin to show early signs of a panic reaction due to the pressure of having to appear. Therefore, public speaking training is very crucial to be held at SMK Darur Rohman with the aim of making students confident to appear bravely in public as public speakers. This training method is held with the presence of speakers, questions and answers between audiences, and speech competitions for students. It can be seen that after the training, students began to open up and dare to appear in public, because in this training several techniques were explained to eliminate panic and fear.